Phasing out an embedded technology: Insights from banning the incandescent light bulb in Europe. (December 2021) - Koretsky, Zahar
Highlights: Phasing-out of a ubiquitous technology, the incandescent light bulb, is studied. ILB scaled down, not phased out, which still impacted the labour force negatively. The case implies similar uneven effects on stakeholders as in technology emergence. Continuity of attractive features can contribute to higher speed of phasing-out. Phase-out is, in principle, reversible due to non-eradication of the technology. Abstract: Opening up the dynamics of phase-outs is important to advance the knowledge about how to navigate phase-outs, how to speed them up and how to ensure justice, all pressing topics in energy transitions. I revisit the case of the incandescent light bulb phase-out in Europe and investigate what processes were involved after the phase-out regulation entered into force (2000–2020). The present study deviates in approach and analytical focus from prior studies of the light bulb phase-out. I use 'technologies-in-practice' as heuristic to trace technology as a processual phenomenon, i.e. as an outcome of processes of co-evolving materiality, meanings, activities and skills integral to them. I find that intentional push for a destabilising meaning (energy inefficiency) of the light bulb, resonant with powerful larger discourse (climate change), and imitation of existing technology by a group of stakeholders was key in the process of light bulb's downscaling. The attachment of new, reinforcing the stability of the configuration, meanings to the light bulb (nostalgic lamp, rough-service lamp) by another group of stakeholders prevented a complete phase-out. I contribute to the existing theoretical literature by offering to put more emphasis on studying the later stages of the technological trajectory, and discussing the winners and losers of the phasing-out.